Resminostat in patients with relapsed or refractory Hodgkin lymphoma: results of the phase II SAPHIRE study. Issue 3 (23rd February 2019) - Walewski, Jan; Paszkiewicz-Kozik, Ewa; Borsaru, Gabriela; Hellmann, Andrzej; Janikova, Andrea; Warszewska, Agnieszka; Mais, Anna; Ammendola, Astrid; Herz, Thomas; Krauss, Babett; Henning, Stefan W.
Abstract: This open-label, single-arm phase II study examined efficacy, safety, pharmacokinetics, and biomarkers of histone deacetylase (HDAC) inhibitor resminostat in patients with relapsed or refractory Hodgkin lymphoma. Thirty-seven heavily pretreated patients received 600 (19 patients) or 800 mg (18 patients) oral resminostat daily for the initial 5 days of 14-day treatment cycles. Objective response rate (ORR) (primary) was 34% reaching disease control in 54% patients. Most patients (69%) showed reduced tumor size and reduced [ 18 F]-FDG uptake in target lesions (71%). Median progression-free survival (PFS) was 2.3 months (95%CI [1.3; 3.3]) and median overall survival (OS) was 12.5 months (95%CI [9.6; 18.6]). Patients who responded or stabilized under resminostat had a 10-month longer OS than patients who progressed. Efficacy assessment, pharmacodynamics, and exploratory biomarker results followed plasma levels, showed target engagement and epigenetic modulations. Common drug-related adverse events (AEs) were nausea, vomiting, anemia, thrombocytopenia, and fatigue, mainly grade 1 or 2.